Effects of compound lactic acid bacteria on the quality and microbial diversity of alfalfa silage in saline-alkali soils - Wang, Si-Yi; Sun, Le; Jiang, Heng; Yang, Guo-Lin; He, Zhen-Nan; Jing, Yuan-Yuan; Gao, Feng-Qin (Frontiers in Microbiology, 2025)
With the rapid development of animal husbandry, forage resources are increasingly scarce. Improving the utilization rate of forage products and silage efficiency of planting is an urgent problem to be solved. This experiment used high moisture alfalfa at the budding stage with a water content of 71.4% from saline-alkali and non-saline-alkali soils as raw materials, setting up four experimental groups: non-saline-alkali alfalfa without additives (HNS-CK), non-saline-alkali alfalfa with compound lactic acid bacteria (Lactobacillus plantarum + Lactobacillus buchneri + Pediococcus pentosaceus + Lactobacillus kimchi, HNS-L4), saline-alkali alfalfa without additives (HS-CK), and saline-alkali alfalfa with compound lactic acid bacteria (HS-L4). After 60 days of silage, the quality and microbial diversity of the silage were tested. The results showed that the dry matter (DM) and lactic acid (LA) of the HNS-L4 group were significantly higher than those of the HS-L4 (P < 0.05), while there was no significant difference in crude protein (CP) between the HNS-L4 group and the HS-L4 (P < 0.05). The neutral detergent fiber (NDF), acid detergent fiber (ADF), pH of the HNS-L4 group were all lower than those of the HS-L4. The results of the microbial community showed that compared with the non-additives group, the Shannon index decreased and the Simpson index increased in the compound lactic acid bacteria group, indicating a significant reduction in microbial diversity in the silage environment (P < 0.05). The dominant bacteria in the HNS-CK and HS-CK groups were Enterobacteriaceae, while the dominant bacteria in the HNS-L4 and HS-L4 groups were Lactobacillus. At the phylum level, the dominant bacteria in alfalfa after lactic acid bacteria treatment were Firmicutes, which were significantly higher than the control group (P < 0.05). Therefore, compound lactic acid bacteria can improve the quality of alfalfa silage in both saline alkali and non-saline-alkali soils, with saline-alkali soils being better than non-saline-alkali soils, and both can reduce microbial diversity.